Analysis of Students’ Morphological Awareness - Naser, Waad Dawood; Gandhi, Nilotpala (Journal of Education Review Provision, 2022)
This research examines the morphological knowledge of the ASE undergraduates learning English as a second language, ESL with reference to simple morphological structure and compound morphological structure. Employing a mixed-methods approach, the research involved a structured test and oral discussions with 70 participants to assess their proficiency in three key areas: total knowledge of words shapes, including both development of individual vocabulary as well as words formation by means of inflections and derivatives. The study affirms that there is evidence of improved understanding of elementary morphemic components; however, there seems to be a growing weakness as the morphological complexity in the forms advances. In particular, the difficulties concern derivational morphology and other advanced features which are very essential for reading and writing levels of language. As for the results of the task, the students demonstrated good performance in the recognition of the simple words as well as morphological tasks such as simple inflections whereas they displayed low performance in tasks that required compounding and derivational affixes and more involved words.